Pendampingan Peningkatan Kemampuan Manajemen Keuangan Di Toko Plastik Silvanoor - Dicky Perwira Ompusunggu; Mona Elisa (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Money is essential in modern life and is needed by everyone to fulfill their needs and desires. There are differences in money management so some people can use it well, and others need to. With proper financial management, individuals can make optimal use of their money. The Silvanoor store in Palangkaraya has good profit potential, but its financial management is still simple, so it is necessary to provide financial management assistance for shop owners and employees. The purpose of this is to improve the financial management capabilities of the Silvanoor plastic shop